Hubungan Komunikasi Interpersonal dan Stres Kerja Dengan Kinerja Pegawai di Kantor Urusan Agama Kecamatan Baturaja Barat - Rr.Dimas Veronica Priharti; Dyah Ayu Putriani; Indra Maulana (Ekonomika, 2021)
Based on the results of data analysis using the multiple correlation calculation shows that the corellation value obtained for Interpersonal Communication (X1) with Employee Performance (Y) of 0.937 means that there is a correlation with very strong criteria between Interpersonal Communication (X1) and Employee Performance (Y). Correlation value obtained for Job Stress (X2) with Employee Performance (Y) of 0.709 means there is a correlation with strong criteria between Job Stress (X2) and Employee Performance (Y). Correlation value obtained for Interpersonal Communication (X1) with Work Stress (X2) of 0.886 means that there is a correlation with very strong criteria between Interpersonal Communication (X1) and Work Stress (X2). While simultaneous testing (together) Interpersonal Communication (X1) and Work Stress (X2) variables with Employee Performance (Y) of 0,000. Then compared to the probability value of 0.05, it turns out the probability value of 0.05 is greater than the value of Sig. F Change or 0.05 ≥ 0,000 then Ho is rejected and Ha is accepted, which means there is a very strong relationship between Interpersonal Communication and Work Stress with Employee Performance in the Office of Religious Affairs in West Baturaja District.